Novel vaccine strategies against aerosol infection with Mycobacterium tuberculosis in mice - Taylor, Jennifer Lynn, author; Orme, Ian, advisor (Colorado State University. Libraries, 2003)
Tuberculosis, although it is an ancient disease, currently kills more people each year than does any other bacterial disease. Unfortunately, Mycobacterium bovis BCG, the only vaccine presently available to fight this pulmonary disease, has proven completely ineffective in certain clinical trials. The overall aim of these studies, therefore, was to investigate the use of novel vaccine strategies against tuberculosis. Because tuberculosis is primarily a pulmonary disease, a novel vaccine was designed to target the lungs by means of a recombinant adenovirus vector expressing the major mycobacterial antigen, Ag85A, in its native form. El-deleted adenovirus vectors expressing either Ag85A (Ad85) or the bacterial β-galactosidase (AdZ) were aerogenically administered to C57BL/6 mice. Initial results showed that both the reporter gene encoding β-galactosidase or the Ag85A gene were expressed by the viruses both in vitro and in the lungs. While the Ad85 vaccine was able to induce strong antibody responses against the Ag85A protein when delivered by the aerosol route, thereby suggesting that recombinant Ag85A was detected by the adaptive immune response, the vaccine was only able to generate significant protection when it was delivered intranasally to anesthetized mice. In addition, this protection was associated with the production of IFNγ in the spleen and an increase in activated CD8 T cells in the lungs. In a second set of studies, prime-boost strategies were performed in order to determine if Ad85 was capable of boosting the immunogenicity and protective efficacy of a DNA vaccine expressing the Ag85A protein (DNA85) or that of a subunit vaccine consisting of Ag85A protein emulsified in monophosphoryl lipid A-squalene adjuvant (Ag85A/MPL-SE). Due to the failure of the Ag85A/MPL-SE subunit vaccine and the DNA85 vaccine to confer any degree of protection on their own, however, it was impossible to determine whether Ad85 was capable of boosting the protective efficacy of these two vaccines. Interestingly, data by flow analysis indicated that the Ad85 boost was able to recruit IFNγ-producing CD4 T cells to the lungs following vaccination with DNA85. Despite this cellular recruitment, however, DNA85+Ad85 vaccinated mice were not protected against challenge with M. tuberculosis. In contrast, BCG vaccinated mice were protected against tuberculosis, and this protection seemed to be correlated with the recruitment of protective CD4 IFNγ T cells to the lungs following BCG vaccination. Additionally, this recruitment of T cells was perhaps indicative of a protective memory response with the capability of potently and swiftly controlling bacilli growth, since after the tuberculosis challenge, the BCG-vaccinated mice had fewer IFNγ-producing CD4 T cells in the lungs compared to unvaccinated controls and the other test groups, none of which were protected against tuberculosis. These combined results indicate that the use of Ad85 in prime-boost studies is worthwhile due to the fact that it induced IFNγ, and perhaps more importantly, it was capable of recruiting a significant number of CD4 IFNγ T cells to the lungs when it was administered as a booster vaccine to DNA85. Furthermore, these studies also demonstrate the importance of employing effective adjuvants in the design of protein subunit vaccines, since Ag85A emulsified in dimethyl dioctadecylammonium bromide (DDA) was almost as protective as BCG compared to Ag85A emulsified in MPL-SE, which was not significantly protective. In addition, the failure of the DNA85 vaccine to protect mice against aerosol challenge with M. tuberculosis was surprising, since this vaccine has been shown to confer significant levels of protection approaching that of BCG in BALB/c and C57BL/6 mice. The inability of DNA85 to confer protection against M. tuberculosis brings into question the usefulness of DNA85 as a realistic vaccine to combat tuberculosis. A successful vaccine against tuberculosis, or any disease for that matter, must provide consistent protection and for practical purposes, it should be easy to administer. In the final series of experiments, we tested another DNA vaccine, which expresses the hsp60 protein from M. leprae, and which has received considerable attention in the last decade due to its ability to significantly protect mice prophylactically and therapeutically against intravenous challenge with M. tuberculosis. The final studies presented here, however, show that the hsp60 DNA vaccine failed to protect mice against a more realistic aerosol infection with M. tuberculosis in either a prophylactic or therapeutic mode. In fact, the hsp60 DNA vaccine, as well as the DNA85 vaccine, induced severe pulmonary necrosis in the lungs reminiscent of the classical Koch reaction when delivered in a therapeutic mode, especially when given to a susceptible mouse strain. Further studies were performed in gene knockout mice to determine what cell populations might be responsible for these foci of necrosis in the lungs after hsp60 DNA vaccination. Preliminary results suggest that B cells play an important part in perhaps protecting hsp60 DNA immunized mice from the pathological effects caused by an, as of yet, undetermined source. The results from these studies suggest that although these DNA vaccines seem to be safe when given prophylactically to naive individuals, when given to individuals who have been previously exposed to tuberculosis, there may be a risk of aggravating M. tuberculosis-associated pulmonary lesions or perhaps triggering reactivation of a latent tuberculosis infection.
Keywords: microbiology; immunology